Student Learning Ethics: Classical Islamic Literature Analysis - Alya Shofi Fathia; Dias Ayu Miftakhul Jannah; Razif Hanani; Heru Prastyo; Muhammad Fahmi (Jurnal Indonesia Sosial Teknologi, 2022)
This article uses literature review through the elaboration of classical texts, and some of literary sources until became this article. It started when there was an ethical degradation that occurred between students and teachers. This article aims to be a guideline for students who are studying. This is felt to be quite important by taking into account the quality of graduates produced by the education units of primary, secondary, and even higher education which slightly decreases in quality when compared to past scholars. Also starting to reduce students' understanding of ethics towards science and themselves when studying. The study in this journal uses a method of study of literature. The study of literature is a way to solve problems by looking through previously produced sources of writing. In other languages, the term for the study of literature is also very familiar with the title library study. Whereas ethics is one of the factors that are believed to affect the level of ease of understanding a science. This condition is the background of writing this article. By reviewing and analyzing the texts of classical books and other literature sources, it was successfully stated that among the ethics that need to be applied to every student are to cleanse themselves of various heart diseases, having the right intentions, choose the right teacher and be ethical in front of the teacher, choose good friends, and earnest in seeking knowledge.